Features of Group Motivation for Criminal Acts Committed on the Grounds of Religious Hatred or Hostility - LEONENKO, Tetiana Ye.; LEONENKO, Maksym I.; SHKUTA, Oleh O.; YURCHYSHYN, Vasyl M. (Journal of Advanced Research in Law and Economics, 2019)
The urgency of the research is that in modern conditions the problem of legal regulation of religious relations is an important subject of attention of international organizations, scholars and the public. The article seeks to identify the features of group motivation for crimes committed on the basis of religious hatred or hostility. The article investigates the nature of social conflicts, identifies the main causes and ways of realizing interreligious conflicts and proves that these conflicts are politicized, and responsibility for resolving religious conflicts should be entrusted, first of all, to the state. The authors conclude that the totalitarian sects are the structural basis for the spread of religious extremism. The article analyzes the peculiarities of the activity of religious sects and reveals the parameters by which such organizations can be characterized as criminal.